Nonlinear micro-mechanical analysis of masonry periodic unit cells. (February 2016) - Drougkas, Anastasios; Roca, Pere; Molins, Climent
Abstract: A model for the analysis of masonry periodic unit cells of several wall and pillar geometrical typologies is proposed. It is based on a micro-mechanical analysis of the masonry cell, which has been divided into cuboids, and coupled with constitutive laws modeling the behavior of the materials in tension and multiaxial compression. The model may be used for the determination of the tensile and compressive strength of masonry composites, in addition to its elastic properties. The results obtained from its application to case studies from the literature are compared in terms of accuracy and computational cost to finite element analyses of the same structures with a favorable outcome. Based on the micro-mechanical model formulations, and taking advantage of their low computational cost, a comprehensive parametric investigation is performed, covering the effects of several material parameters on the compressive strength of masonry. Finally, a closed-form expression for the determination of the compressive strength of masonry based on the properties of the units and the mortar is proposed. Highlights: The orthotropic properties of masonry are derived with very low computational cost. Several different masonry wall and pillar typologies are investigated. The model results are compared to experimental data and FE calculations. A parametric investigation is performed to determine the effect of the mechanical properties of units and mortar to the compressive strength of masonry. Closed form expressions for the determination of the compressive strength of masonry are proposed.